Kajian Kualitatif Tes Hasil Belajar Buatan Guru Biologi MAN di Kota Kendari - Syarif Rizalia; Andi Nuranissa Syam; Nourma Yulita (Journal of Natural Science and Integration, 2021)
The purpose of this study aims is analyzing the content validation, construction validation, and the distribution of cognitive types of learning outcome tests made by the biology teacher of MAN Sekota Kendari in the odd semester of the 2017/2018. This research was conducted at MAN 1 Kendari and MAN Insan Cendekia Kendari. The ex post facto method was used in this research. The sample in this study was a test of biology learning outcomes at MAN Sekota Kendari grade X, XI, and XII in the odd semester of the 2017/2018. The data source in this study was the biology teacher. The instrument used in this research is the qualitative analysis sheet of the correlation test of learning. The data from this research were processed using descriptive analysis techniques. The results showed that in terms of content validation, the percentage of scores for grade X, XI, and XII in all basic competencies of biological material was categorized as very good. In terms of construct validation, the percentage of scores in class X and XII has a very good category and a good category, while class XI is categorized as very good. Furthermore, the comparison of the distribution of the cognitive type of learning result test was not good, namely 1.22: 1.82: 0.21, so it can be concluded that the learning result test made by the biology teacher of MAN Sekota Kendari was correct in terms of its manufacture (in terms of content and construct studies), but not yet. Precise in measuring the distribution of cognitive types of each question that is not yet ideal. Therefore, it is hoped that the biology teacher of MAN Sekota Kendari will also pay attention to the cognitive types on the tests that have been made in order to effectively and efficiently measure students' learning outcomes of biology.Keywords: learning outcomes test, biology teacher.ABSTRAKPenelitian ini bertujuan untuk menganalisis secara kualitatif validasi isi, validasi konstruksi, dan penyebaran tipe kognitif tes hasil belajar buatan guru biologi MAN Sekota Kendari pada semester ganjil tahun pelajaran 2017/2018. Penelitian ini dilaksanakan di MAN 1 Kendari dan MAN Insan Cendekia Kendari. Metode yang digunakan dalam penelitian ini yaitu metode expost facto. Sampel dalam penelitian ini adalah tes hasil belajar biologi MAN Sekota Kendari kelas X, XI, dan XII semester ganjil tahun pelajaran 2017/2018. Sumber data dalam penelitian ini adalah guru biologi. Instrumen yang digunakan dalam penelitian ini yaitu lembar analisis kualitatif korelasi tes hasil belajar. Data hasil penelitian ini diolah dengan menggunakan teknik analisis deskriptif. Hasil penelitian menunjukkan bahwa dari segi validasi isi, persentase perolehan skor kelas X, XI, dan XII di semua komptensi dasar materi biologi terkategori sangat baik. Dari segi validasi konstruk, persentase perolehan skor di kelas X dan XII memiliki kategori sangat baik dan kategori baik, sedangkan kelas XI terkategori sangat baik. Selanjutnya, perbandingan penyebaran tipe kognitif tes hasil belajar belum baik (mengikuti ketentuan) yaitu 1.22 : 1.82 : 0.21, sehingga dapat disimpulkan tes hasil belajar buatan guru biologi MAN Sekota Kendari sudah tepat dari segi pembuatannya (ditinjau dari kajian isi dan konstruk), namun belum tepat dalam mengukur penyebaran tipe kognitif setiap soal yang belum ideal. Oleh karena itu, diharapkan guru biologi MAN Sekota Kendari juga memerhatikan tipe kognitif pada tes yang telah dibuat agar dapat mengukur secara efektif dan efisien hasil belajar biologi siswa. Kata Kunci: tes hasil belajar, guru biologi